The Importance of National Values in Educating Young People to Believe in the Motherland - Akhmadaliyev Berdiali Saidaliyevich (International Journal on Integrated Education, 2022)
National values are a complex socio-spiritual phenomenon that comprehensively covers the language, culture, history, traditions, total material and spiritual wealth, economic, political and spiritual life of nations.